Strengthening E-commerce Customer Satisfaction through Delivery Service Transparency - Regina Emiliana; Efawati, Yen (International Journal Administration, Business & Organization, 2025)
The purpose of this study is to investigate the impact of Real-Time Tracking Systems (RTTS) on customer satisfaction through Last Mile Delivery (LMD) Transparency in the context of E-commerce businesses. The research aims to explore how the integration of real-time tracking affects consumer satisfaction, particularly focusing on the transparency of the delivery process. The sample for this study comprised 112 respondents, all of whom were vocational students in Bandung with prior experience in e-commerce transactions and regular use of RTTS to monitor their product shipments. This study employs a quantitative approach, utilizing correlation and regression analysis to examine the relationships among variables. Data was collected using a structured questionnaire distributed via Google Forms, both directly and through social media platforms, targeting respondents who met the study's inclusion criteria. The findings indicate that the use of RTTS has a significant positive effect on customer satisfaction through enhancing LMD transparency in e-commerce, accounting for 55.6% of the variation in delivery transparency. The remaining 44.4% of the variance is attributed to other factors, suggesting that additional elements beyond RTTS also contribute to the transparency and efficiency of the last-mile delivery process. These results highlight the importance of real-time tracking in improving customer experience and operational transparency in the rapidly growing e-commerce sector.